MicroCT image-generated tumour geometry and SAR distribution for tumour temperature elevation simulations in magnetic nanoparticle hyperthermia. (27th September 2013) - LeBrun, Alexander; Manuchehrabadi, Navid; Attaluri, Anilchandra; Wang, Frank; Ma, Ronghui; Zhu, Liang
Abstract: Objectives: The objective of this study was to develop and test computer algorithms to export micro computed tomography (microCT) images and to generate tumour geometry and specific absorption rate (SAR) distribution for heat transfer simulation in magnetic nanoparticle hyperthermia. Methods: Computer algorithms were written to analyse and export microCT images of 3D tumours containing magnetic nanoparticles. MATLAB® and ProE® programs were used to generate a prototype of the tumour geometry. The enhancements in the microCT pixel index number due to presence of nanoparticles in the tumours were first converted into corresponding SAR values. The SAR data were then averaged over three-dimensional clusters of pixels using the SAS® program. This greatly decreased the size of the SAR file, while in the meantime it ensured that the amount of total energy deposited in the tumour was conserved. Both the tumour geometry and the SAR file were then imported into the COMSOL® software package to simulate temperature elevations in the tumour and their surrounding tissue region during magnetic nanoparticle hyperthermia. Results: A linear relationship was obtained to relate individual pixel index numbers in the microCT images to the SAR values under a specific magnetic field. The generated prototype of the tumour geometry based on only 30 slices of microCT images resembled the original tumour shape and size. The tumour geometry and the simplified SAR data set were successfully accepted by the COMSOL software for heat transfer simulation. Up to 20 °C temperature elevations from its baseline temperature were found inside the tumours, implying possible thermal damage to the tumour during magnetic nanoparticle hyperthermia.